Rice pyramided line IRBB67 (Xa4/Xa7) homeostasis under combined stress of high temperature and bacterial blight - Dossa, Gerbert Sylvestre; Quibod, Ian; Atienza-Grande, Genelou; Oliva, Ricardo; Maiss, Edgar; Vera Cruz, Casiana; Wydra, Kerstin (Springer, 2020)
Rice bacterial blight (BB) caused by Xanthomonas oryzae pv. oryzae (Xoo) implies substantial yield loss to rice. In times of climate change, increasing temperatures are observed and further acceleration is expected worldwide. Increasing temperature often turns into inhibition of host plant defense to pathogens. Recently, a reduced resistance in rice IRBB4 carrying Xa4, but an increase in resistance in IRBB7 carrying Xa7 resistance by increasing temperature has been reported. Influence of high temperature on both R genes (Xa4+Xa7) combined in IRBB67 was analyzed under growth chamber conditions and transcriptomic analysis performed. The pyramided line IRBB67 showed no differences in lesion length between both temperature regimes, demonstrating that non-effectiveness of Xa4 at high temperature did not affect IRBB67 resistance. Moreover, Xa4 complements Xa7 resistance with no Xoo spread in planta beyond the symptomatic area under both temperature regimes in IRBB67. Time course transcriptomic analysis revealed that temperature enhanced IRBB67 resistance to combined heat and Xoo. Our findings highlight altered cellular compartments and point at a role of the cell wall involved in Xoo resistance and heat stress tolerance in both susceptible (IR24) and the resistant (IRBB67) NILs. Interestingly, up-regulation of trehalose-6-phosphatase gene and low affinity cation transporter in IRBB67 suggest that IRBB67 maintained a certain homeostasis under high temperature which may have enhanced its resistance. The interplay of both heat stress and Xoo responses as determined by up-regulated and down-regulated genes demonstrates how resistant plants cope with combined biotic and abiotic stresses.